Effects of Phonics Charts on Senior Secondary School Students’ Achievement in Oral English in Edu, Kwara State - Muritala Imam Suleiman; Muhammed Adam (Britain International for Academic Research (BIAR) Publisher, 2019)
The phenomenon of poor performance in internal and external examinations among Nigerian students, especially, those in the secondary schools, is a matter that has become a source of concern to stakeholders in the education sector in the country. This study therefore investigated the effects of phonics charts on senior secondary school students’ achievement in oral English in Edu, Kwara State. Three objectives and corresponding research questions guided the study. Two hypotheses postulated were tested at 0.05 alpha levels.The quasi-experimental design was adopted using the non-randomised pre/posttest groups design. The population for this study was all senior secondary school students in Edu, Kwara State. The target population for this study was all SSII students in public schools in Lafiagi Emirate,87 students were sampled in their intact classes. The Oral English Achievement Test (OEAT) with a reliability coefficient of 0.69 was used to gather the data for the study. The data collected were analysed using descriptive and inferential statistic methods-mean and standard deviation and the Analysis of Covariance (ANCOVA).The findings obtained from this study revealed that the general achievement level of students (both the experimental and control groups) in Oral English was low in the pre-test. However, in the post-test, the general achievement level of the students that were taught with phonics charts in Oral English was relatively high (32.00), while that of students taught with the conventional method was average (24.78). there was a statistically significant effect of phonics charts on senior secondary school students that were taught Oral English with Phonics charts and those taught without it in Edu, Kwara State(F(1,82)=7.039,p<0.05)Based on the findings of the study, it was recommended among others that necessary attention should be accorded use of phonics charts in the secondary schools, especially for teaching Oral English. Teachers, textbook writers and curriculum planners should emphasis the use of phonics charts for teaching and learning of Oral English in Secondary schools in Kwara State.